Differences Between Portion, Intake Fruit And Vegetable On Packed And School Lunch To Recommended The Balanced Nutrition Guidelines In Sdit Thariq Bin Ziyad - Anggie Maramis Sarahita; Irfanny Anwar (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
Elementary Islamic Primary School (SDIT) Thariq Bin Ziyad is located in the residential area of Pondok Hijau Permai-Bekasi Timur is an Islamic elementary school that has the concept of full day school, where all students spend about 7 hours in school on Monday to Friday. At lunch time students are required to bring lunch from home or attend catering provided by the school. Based on preliminary test results found not that all students bring lunch contain vegetables and fruit or not suitable for the needs of primary school children. The purpose of this study was to differences portion and intake fruit and vegetable on Packed Meal and School lunch to Recommended Balanced Nutrition Guidelines In SDIT Thariq Bin Ziyad. This research uses food weighing method and interview. The sample of this research is students on grade 3 and 4 who bring food for lunch or catering food, amounted to 72 people. Analysis of univariate and bivariate data using Independent Test T-Test. The results showed that there was a difference between vegetable and fruit portion at Packed and School lunch, there was difference of vegetable intake on Packed and school lunch, and there was no difference between fruit intake at Packed and School lunch.